Efficacy Study of Chloroquine to Plasmodium vivax Malaria in Darimu and Bure Districts, Southwest Ethiopia - Yeshanew, Solomon (Infect Drug Resist, 2021)
BACKGROUND: Chloroquine (CQ) is the first line treatment for vivax malaria in Ethiopia. However, the therapeutic efficacy of the drug is now declining. Several reports from different areas of the country showed CQ-vivax treatment failure increasing. This study therefore aimed to provide additional data on the therapeutic efficacy of CQ against Plasmodium vivax malaria from two districts of Southwestern Ethiopia. METHODS: An observational prospective study among P. vivax malaria infected individuals was conducted in two districts of Southwest Ethiopia for a period of 28 follow-up days. Study participants were treated with 25 mg/kg of standard CQ for 3 consecutive days according to the procedure. Microscopic blood film examinations and other clinical assessments were measured within the follow-up period on a weekly basis. RESULTS: A total of 115 patients were enrolled in the study. Sixty-five were from Darimu and 50 were from Bure districts. The majority (67%) of study participants were male and 86.1% (99/115) were below 35 years old. The study revealed that CQ treatment was able to clear vivax malaria parasites and febrile within a week. During the follow-up study period, recurrence of vivax parasitemia was not recorded. However, there was a marked heterogeneity with respect to fever clearance time, parasitemia load, and carriage of parasite gametocyte within 72 hours of post-treatment between the two study areas. CONCLUSION: The present study revealed that CQ has good clinical and parasitological response to vivax malaria in the study areas. Thus, it can be continued as the first line P. vivax malaria treatment. However, further monitoring and evaluation of the drug should be considered.